PENGARUH PENDAPATAN, BEBAN OPERASIONAL DAN LIKUIDITAS TERHADAP LABA BERSIH PADA PERUSAHAAN RETAIL YANG GO PUBLIC DI BURSA EFEK INDONESIA (BEI) PERIODE 2013-2017 - REBECCA EVADINE (LP2MTBM MAKARIOZ, 2021)
This study aims to determine the effect of revenue, operating expenses and liquidity on net profit at Retail Companies thatGo Public on the Indonesia Stock Exchange (IDX) for the period 2013-2017. The research method used is descriptiveanalysis method and the data used is secondary data obtained from the Indonesia Stock Exchange, namely www.idx.co.id.Sampling was conducted by Purposive Sampling as many as 45 Retail companies. The results of this study will show thatthe partial test results (test t) of Operating Income (X1), Operating Expenses (X2) and Liquidity (X3) show the number t >0.05 then Ho is rejected and Ha is accepted, meaning that income, operating expenses and liquidity have a significantpositive effect on net profit (Y). And based on test F, simultaneous test results (test F) that the sig probability value of 0.128 >α0.05, then Ho received and Ha rejected meaning operating income (X1), operating expenses (X2) and liquidity (X3) had nosimultaneous effect on net profit (Y). This is because the level of efficiency of retail companies in carrying out their operationsaffects the revenue generated by the company. If the operational activities are carried out efficiently, then the revenuegenerated by the company will increase.